Fly or cry: is airport noise costly? - Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2009)
Airport noise is costly. Airport location is typically associated with lower property prices. Airport expansion often sparks protests by local residents. In this paper, I provide new evidence on the costs of airport-related noise (and other disamenities of airports) for individuals. In contrast to previous work, I analyze voting results on restricting airport operations. Using data from a referendum on the closure of one of Berlin's inner-city airports, Tempelhof, I find that voting behavior is not primarily explained by exposure to airport disamenities. Rather, strong opposition to closure in the vicinity of Tempelhof indicates that adaptive preferences may be important.
Keywords: D61; D62; H41; I18; R41; 330; noise; preferences; traffic; airports; Flughafen; Verkehrslärm; Kosten-Nutzen-Analyse; Offenbarte Präferenzen; Referendum; Wahlverhalten; Berlin